PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ASSEMBLR EDU PADA PEMBELAJARAN IPAS KELAS IV SD - Sipahutar, Frengki; Lidia Simanihuruk; Zainuddin, Zainuddin; Ananda, Lala Jelita; Afriadi, Putra (Jurnal Merah Putih Sekolah Dasar, 2025)
This research aims to develop an interactive learning media based on Augmented Reality technology using the Assemblr Edu application in the IPAS subject, specifically on the photosynthesis topic. This media was developed to address the issue of low student engagement caused by limited use of varied and technologically enriched media. The research method used is the 4D development model consisting of the Define, Design, Develop, and Disseminate stages. The instruments used in this study include expert validation questionnaires (content and media), teacher and student response questionnaires, and learning outcome tests. The research results showed that the developed media met the criteria of validity, practicality, and effectiveness, and successfully improved the motivation and learning outcomes of 4th-grade students at SDN 060857 Medan Tembung.